2018
DOI: 10.1002/bjs.10897
|View full text |Cite
|
Sign up to set email alerts
|

Patients' preferences for treatment after neoadjuvant chemoradiotherapy for oesophageal cancer

Abstract: Patients are willing to trade off substantial 5-year survival to achieve a reduction in the risk that oesophagectomy is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 39 publications
1
30
0
Order By: Relevance
“…We also found that some participants reported difficulty separating their own recent personal experience of revision surgery from the hypothetical scenarios presented in the questionnaire, as they found it hard to imagine receiving a treatment option that differed from the one that they had received. In terms of methodology, many DCEs are conducted with participants who already have some experience of the treatment attributes under investigation 12 19 20 24. In our study previous experience meant that participants had some appreciation of the attributes being tested.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found that some participants reported difficulty separating their own recent personal experience of revision surgery from the hypothetical scenarios presented in the questionnaire, as they found it hard to imagine receiving a treatment option that differed from the one that they had received. In terms of methodology, many DCEs are conducted with participants who already have some experience of the treatment attributes under investigation 12 19 20 24. In our study previous experience meant that participants had some appreciation of the attributes being tested.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research using discrete choice approaches has explored patient preferences in a surgical context. This has included examination of preferences for surgical versus non-surgical interventions in a range of conditions, such as oesophageal cancer and ulcerative colitis 24 25. Some research has explored preferences for conditions in which there are two surgical options, including for ectopic pregnancy, vaginal wall prolapse and osteoarthritis 26 27.…”
Section: Discussionmentioning
confidence: 99%
“…9 What to do after complete response is still under debate 19 but patients seem to be willing to trade a substantial 5-year survival for a reduction in the risk of a possible esophagectomy. 25 Thus, it appears essential to have precise prognostic markers to satisfy the patients' need of avoiding overtreatment. Several studies have focused on this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, they found that many patients were willing to trade off substantial 5-years survival to achieve a reduction in the risk of esophagectomy. 16…”
Section: Wait and See Vs Surgerymentioning
confidence: 99%